Applying Student Involvement Theory to Intercollegiate Athletics: Astin's Model and Its Relationship to Developmental Issues - Stone, Jeffrey A. (My University, 1987)
The author applied Astin's involvement theory to the experiences of student-athletes.
Keywords: theory